Step
*
1
2
1
1
of Lemma
vs-lift-unique
1. S : Type
2. K : CRng
3. vs : VectorSpace(K)
4. f : S ⟶ Point(vs)
5. h : Point(free-vs(K;S)) ⟶ Point(vs)
6. ∀u,v:Point(free-vs(K;S)).  ((h u + v) = h u + h v ∈ Point(vs))
7. ∀a:|K|. ∀u:Point(free-vs(K;S)).  ((h a * u) = a * h u ∈ Point(vs))
8. ∀s:S. ((h <s>) = (f s) ∈ Point(vs))
9. (h []) = 0 ∈ Point(vs)
10. fs : Base
11. f1 : Base
12. fs = f1 ∈ (as,bs:(|K| × S) List//permutation(|K| × S;as;bs))
13. fs ∈ (|K| × S) List
14. f1 ∈ (|K| × S) List
15. permutation(|K| × S;fs;f1)
⊢ (h fs) = vs-lift(vs;f;f1) ∈ Point(vs)
BY
{ Assert ⌜(h fs) = vs-lift(vs;f;fs) ∈ Point(vs)⌝⋅ }
1
.....assertion..... 
1. S : Type
2. K : CRng
3. vs : VectorSpace(K)
4. f : S ⟶ Point(vs)
5. h : Point(free-vs(K;S)) ⟶ Point(vs)
6. ∀u,v:Point(free-vs(K;S)).  ((h u + v) = h u + h v ∈ Point(vs))
7. ∀a:|K|. ∀u:Point(free-vs(K;S)).  ((h a * u) = a * h u ∈ Point(vs))
8. ∀s:S. ((h <s>) = (f s) ∈ Point(vs))
9. (h []) = 0 ∈ Point(vs)
10. fs : Base
11. f1 : Base
12. fs = f1 ∈ (as,bs:(|K| × S) List//permutation(|K| × S;as;bs))
13. fs ∈ (|K| × S) List
14. f1 ∈ (|K| × S) List
15. permutation(|K| × S;fs;f1)
⊢ (h fs) = vs-lift(vs;f;fs) ∈ Point(vs)
2
1. S : Type
2. K : CRng
3. vs : VectorSpace(K)
4. f : S ⟶ Point(vs)
5. h : Point(free-vs(K;S)) ⟶ Point(vs)
6. ∀u,v:Point(free-vs(K;S)).  ((h u + v) = h u + h v ∈ Point(vs))
7. ∀a:|K|. ∀u:Point(free-vs(K;S)).  ((h a * u) = a * h u ∈ Point(vs))
8. ∀s:S. ((h <s>) = (f s) ∈ Point(vs))
9. (h []) = 0 ∈ Point(vs)
10. fs : Base
11. f1 : Base
12. fs = f1 ∈ (as,bs:(|K| × S) List//permutation(|K| × S;as;bs))
13. fs ∈ (|K| × S) List
14. f1 ∈ (|K| × S) List
15. permutation(|K| × S;fs;f1)
16. (h fs) = vs-lift(vs;f;fs) ∈ Point(vs)
⊢ (h fs) = vs-lift(vs;f;f1) ∈ Point(vs)
Latex:
Latex:
1.  S  :  Type
2.  K  :  CRng
3.  vs  :  VectorSpace(K)
4.  f  :  S  {}\mrightarrow{}  Point(vs)
5.  h  :  Point(free-vs(K;S))  {}\mrightarrow{}  Point(vs)
6.  \mforall{}u,v:Point(free-vs(K;S)).    ((h  u  +  v)  =  h  u  +  h  v)
7.  \mforall{}a:|K|.  \mforall{}u:Point(free-vs(K;S)).    ((h  a  *  u)  =  a  *  h  u)
8.  \mforall{}s:S.  ((h  <s>)  =  (f  s))
9.  (h  [])  =  0
10.  fs  :  Base
11.  f1  :  Base
12.  fs  =  f1
13.  fs  \mmember{}  (|K|  \mtimes{}  S)  List
14.  f1  \mmember{}  (|K|  \mtimes{}  S)  List
15.  permutation(|K|  \mtimes{}  S;fs;f1)
\mvdash{}  (h  fs)  =  vs-lift(vs;f;f1)
By
Latex:
Assert  \mkleeneopen{}(h  fs)  =  vs-lift(vs;f;fs)\mkleeneclose{}\mcdot{}
Home
Index